Islas míticas en relación con Canarias - Martínez Hernández, Marcos (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2010)
In this paper we study some questions of nesology, as the concept of island, the islands in the literature (specifi cally greek and latin) and their typology, particularly the mythic islands, some of them (Isles of the Blest, Hesperides Islands, Atlantis, Fortunate Islands, Saint Brandan) , we analyse connected with the Canary Islands.
Keywords: Nesology; Islands; Typology; Mythic islands; Isles of the Blest; Hesperides Islands; Atlantis; Fortunate islands; Saint Brandan; The Canary Islands